1997
DOI: 10.1093/emboj/16.23.6914
|View full text |Cite
|
Sign up to set email alerts
|

The c-IAP-1 and c-IAP-2 proteins are direct inhibitors of specific caspases

Abstract: The inhibitor of apoptosis (IAP) family of proteins are highly conserved through evolution. However, the mechanisms by which these proteins interfere with apoptotic cell death have been enigmatic. Recently, we showed that one of the human IAP family proteins, XIAP, can bind to and potently inhibit specific cell death proteases (caspases) that function in the distal portions of the proteolytic cascades involved in apoptosis. In this study, we investigated three of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
791
2
11

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,170 publications
(835 citation statements)
references
References 67 publications
31
791
2
11
Order By: Relevance
“…Similar anti-sense studies, or use of dominant-negative mutants (T34A), have confirmed a role for survivin in conferring apoptotic resistance in prostate cancer [31,32]. In the case of c-IAP2, reports have indicated an association between higher expression levels of c-IAP2 and more aggressive disease, consistent with the documented function of this anti-apoptotic protein as a suppressor of caspases [28].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Similar anti-sense studies, or use of dominant-negative mutants (T34A), have confirmed a role for survivin in conferring apoptotic resistance in prostate cancer [31,32]. In the case of c-IAP2, reports have indicated an association between higher expression levels of c-IAP2 and more aggressive disease, consistent with the documented function of this anti-apoptotic protein as a suppressor of caspases [28].…”
Section: Discussionmentioning
confidence: 54%
“…The activity of caspases-3, -7, and -9 is often further regulated by inhibitor of apoptosis protein (IAP) family members (i.e., c-IAP1 [cellular inhibitor of apoptosis protein 1], c-IAP2, XIAP [X-linked inhibitor of apoptosis protein] and survivin) [27,28]. To date, most studies of this family of proteins have focussed on the expression of survivin.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 API2 is a member of the IAP (inhibitor of apoptosis) gene family, and is essential for the suppression of apoptosis. 5 MALT1, a novel gene, may be involved in NF kappa B activation, 6 however, its biological function is not fully elucidated. Recent data have shown that API2-MALT1 fusion leads to an increased inhibition of apoptosis, which thereby helps MALT lymphomas to survive.…”
mentioning
confidence: 99%
“…BIRs contain a highly conserved arrangement of cysteine and histidine residues that belong to a putative zinc-binding fold. BIRs mediate the interactions between IAPs and various other proteins, including caspases and IBM proteins (Roy et al, 1997;Vucic et al, 1997;Salvesen and Duckett, 2002). BIRs also mediate the formation of IAP homodimers, the apparent functional form of these proteins (Hozak et al, 2000).…”
Section: Introductionmentioning
confidence: 99%